Islamic Leadership Values in the Dynamics of Theory and the Development of Educational Organizations - Miskanik, Miskanik; Hafsah, Mohammad Jafar (UII Darullughah Waddawah Pasuruan, 2026)
The integration of Islamic leadership values in educational organizations responds to the limitations of modern organizational paradigms that focus too much on efficiency and rationality while ignoring moral and spiritual aspects. The purpose of this study is to examine how the values of trustworthiness, justice, consultation, and good example can improve organizational effectiveness and support the character development of students. The method used is library research with a descriptive-analytical approach by reviewing literature on organizational theory and Islamic leadership to build a clear conceptual understanding. The results show that these Islamic leadership values can strengthen managerial practices, create an ethical and participatory organizational culture, and support educational processes that aim for common good. The conclusion is that applying these values creates a more holistic organizational model that balances professionalism and spirituality. The implication is that educational organization theories should include moral and spiritual dimensions as important parts of modern institutional management.